Production and Preliminary Characterization of Linseed Mucilage-Based Films Loaded with Cardamom (Elettaria cardamomum) and Copaiba (Copaifera officinalis) - Treviño Garza, Mayra Zulema; Saldívar Vázquez, Ana Karen; López Villarreal, Sonia Martha; Lara Banda, María del Refugio; Elizondo Luévano, Joel Horacio; Chávez Montes, Abelardo; Báez González, Juan Gabriel; Rodríguez Luis, Osvelia Esmeralda (MDPI, 2023)
In this research, developed linseed mucilage (M)-based films loaded with E. cardamom (MCA), C. officinalis (MCO), and co-loaded with both compounds (MCACO) were evaluated. The incorporation of the active compounds modified the color (redness–greenness, and yellowness); however, the thickness remained constant in all treatments (0.0042–0.0052 mm). In addition, the solubilization time of the films (in artificial saliva) to release the active compounds fluctuates between 9 and 12 min. Furthermore, the incorporation of bioactive compounds increased the total phenolic content and antioxidant activity (DPPH and ABTS, respectively), mainly in MCA (inhibition of 81.99 and 95.80%, respectively) and MCACO (inhibition of 47.15% and 39.73%, respectively). In addition, the incorporation of these compounds also decreased the hardness (39.50%–70.81%), deformation (49.16%–78.30%), and fracturability (39.58%–82.95%). On the other hand, it did not modify the adhesiveness, except in MCO. Moreover, SEM micrographs showed a more homogeneous structure in the MCO films among the films that contained CA in the formulation (heterogeneous structure with the presence of protuberances). Finally, due to the previously reported pharmacological properties of E. cardamomun and C. officinalis, the films developed in this study could have an application as a wounddressing in dentistry.